2015
DOI: 10.3390/ijms160818628
|View full text |Cite
|
Sign up to set email alerts
|

ALS-Linked P56S-VAPB Mutation Impairs the Formation of Multinuclear Myotube in C2C12 Cells

Abstract: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neurodegenerative disorder that affects upper and lower motor neurons. Since motor neurons target skeletal muscles, the maintenance system of muscles is disturbed in ALS; however, the mechanism by which this occurs is unknown. In the present study, we investigated the effects of ALS-associated P56S-vesicle-associated membrane protein-associated protein B (VAPB) (P56S-VAPB) on the IRE1-XBP1 pathway, which is involved in the unfolded protein response (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Moreover, the IRE1a-dependent pathway was impaired in C2C12 cells transfected with mutant VAPB, which is a cause of familial ALS involved in vesicle trafficking. This occurred in association with a limited capacity to form myotubes, thus suggesting that the dysfunction of the unfolded protein response might interfere with the maintenance of muscle integrity in ALS (115).…”
Section: Multiple Pathways Lead To Als Muscle Degenerationmentioning
confidence: 99%
“…Moreover, the IRE1a-dependent pathway was impaired in C2C12 cells transfected with mutant VAPB, which is a cause of familial ALS involved in vesicle trafficking. This occurred in association with a limited capacity to form myotubes, thus suggesting that the dysfunction of the unfolded protein response might interfere with the maintenance of muscle integrity in ALS (115).…”
Section: Multiple Pathways Lead To Als Muscle Degenerationmentioning
confidence: 99%
“…Quantitative analyses were performed as described previously using ImageJ software from the NIH (Tokutake et al, ). C2C12 cells that had been immunostained for myosin heavy‐chain (MHC) and stained with DAPI were analyzed quantitatively.…”
Section: Methodsmentioning
confidence: 99%
“…C2C12 mouse myoblasts were obtained from DS Pharma Biomedical (Osaka, Japan). The cells were cultured as described previously [30]. Briefly, the cells were cultured in growth medium (DMEM/FBS 10%) under 5% CO 2 at 37 • C; differentiation was induced by changing the medium (DMEM/HS 2%) once the cells reached confluency.…”
Section: Cell Culturementioning
confidence: 99%
“…In a previous study, we found that C2C12 mouse skeletal muscle cells overexpressing the P56S-missense mutated vesicle-associated membrane protein/synaptobrevin-associated membrane protein (VAPB), which is the causative gene of familial amyotrophic lateral sclerosis (ALS) [29], exhibit marked myotube formation disruption and IRE1 activation inhibition [30]; this suggests that IRE1 positively controls myogenic differentiation as well as other UPR-sensor factors. Acosta et al reported that overexpression of spliced XBP1 suppresses C2C12 myogenic differentiation [31].…”
Section: Introductionmentioning
confidence: 99%